Changes in Gallbladder Motility and Gallstone Formation Following Laparoscopic Gastric Banding for Morbid Obesity. (1st May 2003) - Al-Jiffry, Bilal O; Shaffer, Eldon A; Saccone, Gino TP; Downey, Peter; Kow, Lilian; Toouli, James
Abstract : Morbid obesity is associated with cholesterol gallstone formation, a risk compounded by rapid weight loss. Laparoscopic gastric banding allows for a measured rate of weight loss, but the subsequent risk for developing gallstones is unknown. METHOD: Twenty-six normal-weight volunteers (body mass index [BMI] less than 30) were compared with 14 morbidly obese patients (BMI greater than 40). Gallbladder volumes were measured ultrasonographically, after fasting and following stimulation with intravenous cholecystokinin-octapeptide (CCK-8). RESULTS: Preoperatively, fasting gallbladder volume and residual volume after CCK stimulation were both two times greater in the obese group (P<0.02 versus controls). Per cent gallbladder emptying was not different. Gallbladder refilling was four times higher in the obese patients (P<0.01). By six weeks postoperatively, the obese patients lost 1.4±0.1% body weight per week. Gallbladder emptying decreased 18.4% (80.3±3.9% to 65.5±6.9%; P<0.05); residual volume rose one-third (not significant), and refilling fell 60.5% (0.43±0.09 to 0.26±0.04 mL/min; P=0.07). Three patients with weight losses of greater than 1.7% per week developed gallstones; gallbladder emptying fell outside the 95 percentile. By six months, weight loss slowed to 0.5±0.1% per week; gallbladder motility improved modestly. No further stones developed. CONCLUSION: Rapid weight loss following laparoscopic gastric banding impairs gallbladder emptying and when pronounced, gallstones form by six weeks postoperatively. The accompanying reduction in gallbladder emptying, increased gallbladder residual volume and decreased refilling promote gallbladder stasis and hence stone formation.